Early-blind Individuals Show Impaired Performance in Wine Odor Categorization. (15th October 2018) - Manescu, Simona; Poupon, Daphnée; Ballester, Jordi; Abdi, Hervé; Valentin, Dominique; Lepore, Franco; Frasnelli, Johannes
Highlights: Early-blind individuals had more difficulty to categorize wine odors. Early-blind individuals do not seem to have higher olfactory sensitivity. Red wines were easier to classify followed by white and then rosé wines. Abstract: Blind individuals display superior sensory abilities in other modalities, yet results remain contradictory regarding their performance on olfactory tasks. Using complex ecological olfactory tasks, we evaluated the impact of blindness on olfactory performance. We tested 12 early-blind individuals ( M  = 49, SD  = 13.09) and 12 sighted controls ( M  = 49, SD  = 14.31) who were all blindfolded. Based solely on the wine odors, participants evaluated 24 pairs of wine and determined if both samples belonged to the same category (red wine, white wine, or rosé wine) or not ( odor categorization ), and if so, whether they were identical or not ( odor differentiation). Then, they had to classify 15 different wines (5 red, 5 white and 5 rosé) into red, white, and rosé wines ( odor classification ). Blind individuals ( d ′: M  = 1.3, SD  = 1.2) presented lower scores compared to sighted controls ( M  = 2.2 SD  = 0.8; p  < .05) in the odor categorization task, but no group difference was observed for the other tasks. For all participants, red wine odors were the easiest to classify (1.8 ± 1.0), followed by white wine odors (0.5 ± 0.6) and finally rosé wine odors (blind and sighted; F [2; 44] = 11.9, p  < .001). In summary, early-blind individuals had a harder time to categorize wine odors. This could be explained by a different construction of internal reference categories for wine in early-blind individuals. Finally, this research is in line with the notion of the absence of higher olfactory sensitivity in blind individuals.